Quantitative Ultrasound Analysis of Proximal and Distal Cervical Tissue Echogenicity in Premature Cervical Remodeling. (16th April 2018) - Blitz, Matthew J.; Ghorayeb, Sleiman R.; Pachtman, Sarah L.; Murphy, Megan; Rahman, Zara; Prasannan, Lakha; Sison, Cristina P.; Vohra, Nidhi; Rochelson, Burton
Abstract : Objectives: To determine whether a novel, noninvasive quantitative ultrasound (US) technique can detect differences in proximal and distal cervical tissue echogenicity in women with and without a shortened cervical length (CL). Methods: We conducted a retrospective case‐control study of singleton pregnancies at 16 to 26 weeks' gestation in which a transvaginal US examination was performed to measure CL from 2013 to 2015. Initial CLs in cases and controls were less than 2.5 cm and 2.5 cm or greater, respectively. For each US image, a region of interest was selected in the proximal and distal cervical stroma, in both the anterior and posterior cervical lips. The Floyd‐Steinberg dithering algorithm transformed grayscale pixels in each region of interest into a binary map. A histogram tabulated the number of black and white pixels, allowing determination of the percent echogenicity. The difference in the percent echogenicity was calculated by subtracting the distal cervical echogenicity (average of anterior and posterior lips) from the proximal cervical echogenicity (average of anterior and posterior lips). Results: Ultrasound images from 177 women were analyzed. There was a difference in the percent echogenicity ( P < .0001) when comparing women with a short cervix (mean ± SD, 9.8 ± 10.1; n = 102) to women with a normal CL (17.2 ± 9.5; n = 75). Differences were attributable to changes in proximal ( P < .008) rather than distal cervical echogenicity. Regardless of CL, the proximal cervix was more echogenic than the distal cervix. Conclusions: A quantitative US analysis of cervical tissue can detect differences in echogenicity between the proximal and distal cervix in the second trimester. Proximal cervical echogenicity is lower with CL of less than 2.5 cm compared to a normal CL.